REPRODUCIBILITY OF THE RESULTS OF MICROBE IDENTIFICATION BY MALDI-TOF MASS SPECTROMETRY DEPENDING ON GROWTH CONDITIONS BY THE EXAMPLE OF Geobacillus stearothermоphilus - K. V. Starostin; E. A. Demidov; A. S. Rozanov; A. V. Bryanskaya; S. E. Peltek (Вавиловский журнал генетики и селекции)
Rapid and accurate methods of microorganism identification are essential in various human activities. They include primarily clinical diagnostics. In addition, they are in demand in environment monitoring, harmacology, food industry, research, etc. There are diverse approaches to microbe identification: phenotyping, genotyping, chemotaxonomy, direct protein profiling, etc. In this work, the effects of various growth conditions, such as temperature, growth time, and nutrition medium, on the reproducibility of microbe identification by MALDI-TOF mass spectrometry are considered by the example of three Geobacillus stearothermоphilus strains.